The efficiency of D1(+) lymphadenectomy in signet ring cell carcinoma: comparison of postoperative early and late outcomes between standard lymphadenectomy and D1(+) lymphadenectomy. Issue 1 (1st January 2021) - Morkavuk, Şevket Barış; Çulcu, Serdar; Tez, Mesut; Ünal, Ali Ekrem
ABSTRACT: Signet ring cell carcinoma (SRCC) is a poorly cohesive subtype of gastric cancer. It is more aggressive than other types of gastric cancer. There is no special method for its treatment, but gastrectomy and lymphadenectomy is the standard approach. The aim of this study is to investigate postoperative outcomes of D1 lymphadenectomy and D1(+)lymphadenectomy in gastric SRCC. A total of 358 cases whohad a gastrectomy performed forthe diagnosis of gastric cancer between 2013 and 2019 in Ankara University Medical Faculty, Surgical Oncology Department were retrospectively investigated. In all, 128 of the cases had SRCC in the final pathology. We separated the cases into two types, D1 lymphadenectomy and D1(+) lymphadenectomy. The 5-year survival, early mortality, hospital mortality and postoperative complication rates were evaluated. There were 59 patients in the D1 group and 64 patients in the D1(+) group.Metastatic lymph node amount and therefore N stage was found to be significantly higher in the D1(+) group (p=0.00 and p=0.03, respectively). Postoperative chyle fistula was found to be significantly higher in the D1(+) group (p=0.003). There was no statistically significant difference between the groups with regard tomean survival (p=0.065);the 5-year mean survival was 21% in the D1 group and 7% in the D1(+) group. Present findings suggest that extended lymphadenectomy does not provide a benefit in cases of SRCC.